2004
DOI: 10.1021/la035562l
|View full text |Cite
|
Sign up to set email alerts
|

Phase Behavior of a Mixture of Poly(isoprene)−Poly(oxyethylene) Diblock Copolymer and Poly(oxyethylene) Surfactant in Water

Abstract: The phase behavior of a mixture of poly(isoprene)-poly(oxyethylene) diblock copolymer (PI-PEO or C250EO70) and poly(oxyethylene) surfactant (C12EO3, C12EO5, C12EO6, C12EO7, and C12EO9) in water was investigated by phase study, small-angle X-ray scattering, and dynamic light scattering (DLS). The copolymer is not soluble in surfactant micellar cubic (I1), hexagonal (H1), and lamellar (Lalpha) liquid crystals, whereas an isotropic copolymer fluid phase coexists with these liquid crystals. Although the PI-PEO is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
23
0

Year Published

2004
2004
2010
2010

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 23 publications
(32 reference statements)
2
23
0
Order By: Relevance
“…The former result is similar to literature findings for C 12 E 5 micelles containing dodecane 19 and PI-PEO. 22 As pointed out by Menge et al, the decrease of R H along with M w is considered due to a transition from wormlike micelles to microemulsion droplets. The incorporation of ndodecane into the cylindrical micelles may cause increase of micellar diameter and then decrease in hydrophilic interaction among polyoxyethylene tails of C 12 E 6 molecules and solvent water, resulting in decrease of solubility of the micelles.…”
Section: Dynamic Light Scatteringmentioning
confidence: 99%
See 1 more Smart Citation
“…The former result is similar to literature findings for C 12 E 5 micelles containing dodecane 19 and PI-PEO. 22 As pointed out by Menge et al, the decrease of R H along with M w is considered due to a transition from wormlike micelles to microemulsion droplets. The incorporation of ndodecane into the cylindrical micelles may cause increase of micellar diameter and then decrease in hydrophilic interaction among polyoxyethylene tails of C 12 E 6 molecules and solvent water, resulting in decrease of solubility of the micelles.…”
Section: Dynamic Light Scatteringmentioning
confidence: 99%
“…Kunieda et al 21,22 studied the size evolution of the C 12 E 5 , C 12 E 6 , C 12 E 7 , and C 12 E 9 micelles with addition of poly(isoprene)-poly(oxyethylene) diblock copolymer (PI-PEO or C 250 E 70 ) by DLS measurements. Their results reveal that the (apparent) hydrodynamic radius R H,app of the C 12 E 5 micelles becomes smaller at low PI-PEO content up to weight fraction of 0.2, passes through a minimum, and then increases with increasing PI-PEO content.…”
mentioning
confidence: 99%
“…Phase behavior and self-assembled structures of a variety of surfactants including conventional poly(oxyethylene)-type nonionic surfactants in aqueous systems were extensively studied in the past [9][10][11][12][13] . It has been found that the self-assembled structures of surfactants are influenced by the composition, temperature, and poly(oxyethylene) chain length.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, this quantity for Rz(EO) 15 is equal to 0.002% wt. Increase of the ethoxylation degree causes decrease of micellesÕ size [17].…”
Section: Micellar Solutions and Lyotropic Liquid Crystalsmentioning
confidence: 99%